2017
DOI: 10.1002/bjs.10318
|View full text |Cite
|
Sign up to set email alerts
|

Bowel function and quality of life after local excision or total mesorectal excision following chemoradiotherapy for rectal cancer

Abstract: Patients who underwent local excision had a better quality of life and bowel function than those who underwent mesorectal excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 35 publications
2
34
0
Order By: Relevance
“…The results indicate that LE plus CRT is clearly superior to TME in terms of maintaining patients’ anal function. Pucciarelli et al 27 showed that patients who underwent CRT followed by LE had better QoL and bowel function than those who underwent CRT followed by mesorectal excision. Their study used the QoL questionnaire-specific colorectal module of the European Organization for Research and Treatment of Cancer and the Memorial Sloan–Kettering Cancer Center Bowel Function Instrument.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that LE plus CRT is clearly superior to TME in terms of maintaining patients’ anal function. Pucciarelli et al 27 showed that patients who underwent CRT followed by LE had better QoL and bowel function than those who underwent CRT followed by mesorectal excision. Their study used the QoL questionnaire-specific colorectal module of the European Organization for Research and Treatment of Cancer and the Memorial Sloan–Kettering Cancer Center Bowel Function Instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been an increasing interest in organ‐preserving treatment strategies, such as the watch‐and‐wait approach and transanal local excision for patients who show an excellent response to preoperative CRT. Organ‐preserving treatment can significantly improve patient quality of life by reducing TME‐related surgical morbidity, bowel and urogenital dysfunction, and the risk of definitive colostomy. On the other hand, there is a need to develop a new treatment strategy to improve CRT effects in non‐responders.…”
Section: Introductionmentioning
confidence: 99%
“…There are some pros and cons of a NOM in these cases. Firstly, avoiding surgery prevents, at least temporarily, the patient from facing the possible consequences of a triple-modality treatment on bowel, urinary and sexual function and its impact on quality of life [ 24 ]. The low anterior resection syndrome (LARS), which is characterised by symptoms such as faecal incontinence, emptying difficulties, urgencies and fragmented bowel movements, is a recognised entity and is seen in as much as 90% of patients who undergo an anterior resection [ 25 27 ].…”
Section: Patient Selection For Preoperative Therapymentioning
confidence: 99%